STRATEGI PENINGKATAN KEUNGGULAN KOMPETITIF UMKM MELALUI KAPASITAS INOVASI DENGAN PERSPEKTIF GENDER - Yusnita, Maya; Wahyudin, Nanang (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2019)
The purpose of this study is to analyze the effect of innovation capacity on the competitive advantage of MSMEs as well as to determine differences in innovation capabilities based on a gender perspective. Research respondents were 60 micro business operators in Bangka Regency. Methods of data collection through questionnaires and interviews. Data were processed using linear regression analysis and the Mann-Whitney Test. The results showed that the capability of innovation had a significant effect on the competitive advantage of microbusinesses in Bangka Regency. In terms of gender, there was no difference in innovation capabilities between male and female microenterprise entrepreneurs in Bangka Regency. Keywords: innovation capacity, competitiveness, gender